PENGARUH NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Dian Pangesti; Untung Sriwidodo; Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the significance of the effect of net profit margin, debt to equity ratio, and firm size on firm value and analyze the significance effect of net profit margin and debt to equity ratio on firm value with firm size as a moderating variable. This research is an empirical study on companies listed on the Jakarta Islamic Index on the Indonesia Stock Exchange in the 2015 – 2018 period. The research sample of 19 companies with purposive sampling technique. Data collection techniques used documentation. Data analysis uses multiple linear regression and absolute difference test. The results of this study indicate that net profit margin has a positive and significant effect on firm value. Debt to equity ratio has a positive and significant effect on firm value. Company size has a negative and significant effect on firm value. Net profit margin, debt to equity ratio, and company size simultaneously have positive and significant effect on firm value. Company size does not moderate the effect of net profit margin on firm value. Company size does not moderate the effect of debt to equity ratio on firm value